2016
DOI: 10.5704/moj.1603.009
|View full text |Cite
|
Sign up to set email alerts
|

Transtubular Transoral Surgery for Excision of a Dystrophic Os Odontoideum: A Case Report

Abstract: Transoral approach to the cervico-medullary junction is a well-established procedure. However oropharyngeal complications in the form of soft tissue morbidity postoperatively do occur. We report a case of a teenage boy with traumatic quadriparesis secondary to compression of the cervico-medullary junction by an os odontoideum. Decompression was done via transoral approach through a tubular retractor system, hence obviating the need for the splitting or separate retraction of the soft palate and minimised the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The tubular retractor through the transoral route has been described in only 1 previous report to achieve a microscopic anterior odontoidectomy through a midline pharyngeal incision. 13 Endoscopic endonasal approaches (EEAs) to the midline cervical spine and CVJ are well described and offer the advantage of preventing dysphagia associated with the transoral approach. The latter is believed to be caused by an injury of the neural plexus formed by the primary pharyngeal motor nerves.…”
Section: Discussionmentioning
confidence: 99%
“…The tubular retractor through the transoral route has been described in only 1 previous report to achieve a microscopic anterior odontoidectomy through a midline pharyngeal incision. 13 Endoscopic endonasal approaches (EEAs) to the midline cervical spine and CVJ are well described and offer the advantage of preventing dysphagia associated with the transoral approach. The latter is believed to be caused by an injury of the neural plexus formed by the primary pharyngeal motor nerves.…”
Section: Discussionmentioning
confidence: 99%
“…An ossicle located in the position of the normal odontoid is referred to as orthotopic, and considered dystopic if it appears near the occiput in the area of the foramen magnum. The incidence of os odontoideum is unknown because the lesion is usually asymptomatic [8] A review of the literature fails to disclose any solid evidence of aetiology of Os Odontoideum [9]. Kirlew et al [10] published a case of os odontoideum among homozygot twin with fusion of posterior arch of C2 and C3.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al reported oropharyngeal complications in 75% patients who had undergone splitting of soft palate compared to 15.4% of patients who did not undergo splitting of the soft palate 6 . Ariffin et al reported the use of a tubular retractor to provide an “access surgery” for microsurgical transoral excision of os odontoideum by inserting the right length tubular retractor directly into the mouth obviating the need to split the soft palate as the tubular retractor naturally pushes away the soft palate, the uvula and the pillars of the tonsils when its “docks” down on the oropharynx 7 . The surgery was complicated by durotomy managed by tissue sealant.…”
Section: Introductionmentioning
confidence: 99%